Posisi Taman Pendidikan Al-Qur’an (TPA) dalam Sistem Pendidikan Islam Nonformal di Indonesia - Dewi Wulandari; Hamidah; Rodhatul Jennah (STKIP Subang, 2025)
Taman Pendidikan Al-Qur’an (TPA) is one of the nonformal Islamic educational institutions that has grown and developed extensively within Indonesian society, particularly in responding to the need for basic religious instruction outside the formal education system. The existence of TPA is not merely limited to providing Qur’anic literacy, but also plays a strategic role in shaping students’ religious character from an early age. Nevertheless, the position of TPA within the nonformal Islamic education system is often understood in a fragmented manner and has not been examined comprehensively within the framework of the national education system. This study aims to analyze and clarify the position of TPA within the structure of nonformal Islamic education in Indonesia, focusing on its functions, roles, and contributions to strengthening Islamic education at the community level. The research employs a qualitative approach using library research, involving a critical analysis of educational regulations, academic literature, and relevant documents related to nonformal Islamic education. The findings indicate that TPA occupies a strategic position as a community-based nonformal Islamic educational institution that complements and reinforces Islamic religious education provided by schools and families. Furthermore, TPA serves as a medium for transmitting Islamic values that are contextual and responsive to social needs, thereby affirming its relevance and significance within the system of nonformal Islamic education in Indonesia.